2020
DOI: 10.3390/app10217577
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hemorrhage Detection in Head CT Using Double-Branch Convolutional Neural Network, Support Vector Machine, and Random Forest

Abstract: Brain hemorrhage is a severe threat to human life, and its timely and correct diagnosis and treatment are of great importance. Multiple types of brain hemorrhage are distinguished depending on the location and character of bleeding. The main division covers five subtypes: subdural, epidural, intraventricular, intraparenchymal, and subarachnoid hemorrhage. This paper presents an approach to detect these intracranial hemorrhage types in computed tomography images of the head. The model trained for each hemorrhag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 27 publications
(46 reference statements)
0
28
0
Order By: Relevance
“…Finally, a computation time (CT) analysis of the AIMA-ICHDC technique with other ICH detection models is shown in Table 3 and Figure 12 [ 27 31 ]. From the figure, it can be observed that the SVM, deep CNN, and WEM-DCNN techniques have required higher CTs of 1.483 min, 1.284 min, and 1.268 min, respectively.…”
Section: Performance Validationmentioning
confidence: 99%
“…Finally, a computation time (CT) analysis of the AIMA-ICHDC technique with other ICH detection models is shown in Table 3 and Figure 12 [ 27 31 ]. From the figure, it can be observed that the SVM, deep CNN, and WEM-DCNN techniques have required higher CTs of 1.483 min, 1.284 min, and 1.268 min, respectively.…”
Section: Performance Validationmentioning
confidence: 99%
“…Radiologist usually needs from 15 to 30 minutes to diagnose a patient and inform about it in writing. Diagnosis of ICH has been a subject of several papers and is a field of intensive research using traditional techniques [8] and deep learning [22][23][24][25]. The solution [36] has AUC 0.846 (CI 0.837-0.856).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some studies have been published on this topic, and many researchers have started to pay attention to it. Among many others, we can cite [22], where the authors use a fully convolutional neural network for classification and segmentation with examination of ICH with computed tomographies; [23] where the InceptionV3 and DenseNet Deep Learning models for dealing with CT; or [24], where the authors combine convolutional neural networks with other machine learning techniques to deal with ICH detection. In [25], the authors use a Dense U-net architecture for the detection of ICH.…”
Section: Deep Learning For the Detection Of Intracranial Hemorrhagementioning
confidence: 99%
“…Accurate and fast diagnosis is crucial as 50% of patients' death happen within 24 hours 35 to 52 % of patients enters in critical zone and die within a month as mortality reaches up to 60% after 30 days [2].To perform accurate diagnosis, first stage examination is performed by a physician using non-contrast computed tomography (CT) analysis. CT image analysis helps to identify and locate the bleeding location inside the brain [3].…”
Section: Introductionmentioning
confidence: 99%